High prevalence of Schistosoma japonicum infection in Carabao from Samar Province, the Philippines: implications for transmission and control. - Catherine A Gordon; Luz P Acosta; Darren J Gray; Remigo M Olveda; Blanca Jarilla; Geoffrey N Gobert; Allen G Ross; Donald P McManus (Public Library of Science (PLoS), 2012)
Schistosoma japonicum is endemic in the Philippines, China and Indonesia, and infects more than 40 mammalian host species, all of which can act as reservoirs of infection. In China, water buffaloes have been shown to be major reservoirs of human infection. However, in the Philippines, carabao have not been considered important reservoir hosts for S. japonicum due to the low prevalence and infection intensities reported, the only exception being a qPCR-based study indicating 51% of carabao were S. japonicum-positive. However, the low prevalence found for the same animals when using conventional copro-parasitological techniques means that there is still confusion about the role of carabao in the transmission of schistosomiasis japonicum. To address this inconsistency, and to shed light on the potential role of carabao in the transmission of S. japonicum in the Philippines, we undertook a pilot survey, collecting fecal samples from animals in Western Samar Province and we used a combination of molecular and copro-parasitological techniques to determine the prevalence and intensity of S. japonicum. We found a high prevalence of S. japonicum in the carabao using a validated real-time PCR (qPCR) and a copro-parasitological tool, the formalin-ethyl acetate sedimentation (FEA-SD) technique. A much lower prevalence of S. japonicum was recorded for the same fecal samples using conventional PCR, the Kato-Katz technique and miracidial hatching. These results suggest that, due to their low diagnostic sensitivity, traditional copro-parasitological techniques underestimate infection in carabao. The use of FEA-SD and qPCR provides a more accurate diagnosis. Based on these findings, the role of bovines in the transmission of S. japonicum appears to be more important in the Philippines than previously recognized, and this may have significant implications for the future control of schistosomiasis there, particularly as, in contrast with previous surveys, we found an unprecedented high prevalence of S. japonicum in humans.